Enhance the chromatic uniformity and luminous efficiency of WLEDs with triple-layer remote phosphor structures - Nguyen Thi Phuong Loan; Anh Tuan Le (Institute of Advanced Engineering and Science, 2020)
The angular color uniformity (ACU) with the ability to evaluate chromatic performance of WLED has become an important target to achieve in producing higher-quality WLEDs. This paper studies the ACU enhancing effects of novel triple-phosphor configuration in lighting devices with remote phosphor structure. Moreover, the optical influences of remote phosphor structure with three phosphor layers (TL) on WLEDs properties are calculated and compared to the dual-layer (DL) one for reference. The experiments are applied to devices at 5 distinct correlated color temperature ranging from 5600-8500 K. The results presented that DL structure attains better color rendering index (CRI) than the TL one. Meanwhile, in terms of color quality scales (CQS), TL model shows higher values at all ACCTs, compared to the DL. Moreover, the luminous flux of DL configuration is lower than that of TL structure. In addition, the diversion of color temperature depicts as D-CCT in TL structure is much better than the value in DL structure, especially at high ACCT as 8500 K, which means TL is good for chromatic uniformity of high ACCTs WLEDs. These results proved that the triple-layer structure is superior and more effective to apply for acquiring the enhancement of WLEDs package.